Transcatheter PFO closure for cryptogenic stroke: current approaches and future considerations - Eltelbany, Moemen; Gattani, Raghav; Ofosu-Somuah, Araba; Damluji, Abdulla; Epps, Kelly C.; Batchelor, Wayne B. (Frontiers in Cardiovascular Medicine, 2024)
Patent Foramen Ovale (PFO) is a common congenital atrial septal defect present in 20%–35% of the general population. Although generally considered a benign anatomic variant, a PFO may facilitate passage of a thrombus from the venous to arterial circulation, thereby resulting in cryptogenic stroke or systemic embolization. A PFO is detected in nearly one half of patients presenting with cryptogenic stroke and often considered the most likely etiology when other causes have been excluded. In this review, we discuss the contemporary role of transcatheter closure of PFO in the treatment of cryptogenic stroke, including devices currently available for commercial use in the United States (Amplatzer PFOTM Occluder and GoreTM Cardioform Septal Occluder) and a novel suture-mediated device (NobleStitchTM EL) under clinical investigation. To provide the best care for cryptogenic stroke patients, practitioners should be familiar with the indications for PFO closure and corresponding treatment options.